2000
DOI: 10.1046/j.1432-1327.2000.01631.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the internalization of neuropeptide Y on neuroblastoma cell line SK‐N‐MC

Abstract: Neuropeptide Y (NPY) is an important neuromodulator in the central and peripheral nervous system. The peptide acts through different NPY receptor subtypes (Y1±Y5, y6) that belong to the family of G protein-coupled receptors. In general, cellular responses to prolonged exposure to agonists of G protein-coupled receptors are attenuated, often through internalization of the receptors and their bound ligands. In this study, a fluorescent labeled NPY derivative was synthesized and characterized to investigate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 22 publications
(23 reference statements)
2
43
0
Order By: Relevance
“…The hY 1 receptor was found to be rapidly internalized upon agonist stimulation by different groups (Fabry et al , 2000 ;Gicquiaux et al , 2002 ;Bohme et al , 2008 ;Ouedraogo et al , 2008 ;Lindner et al , 2009 ;Kilpatrick et al , 2010 ;Lecat et al , 2011 ;Lundell et al , 2011 ), consistent with the results that were obtained for its orthologs in the rat (Holliday and Cox , 2003 ;Pheng et al , 2003 ;Holliday et al , 2005 ;Kilpatrick et al , 2012 ) or guinea pig (Parker et al , 2001(Parker et al , , 2002b. Several studies on the internalization mechanism revealed that the Y 1 receptor undergoes clathrin-dependent endocytosis in an Arr3-dependent fashion and is transported back to the cell membrane, involving direct and indirect recycling mechanisms (Gicquiaux et al , 2002 ;Berglund et al , Pheng et al , 2003b ;Holliday et al , 2005 ;Ouedraogo et al , 2008 ;Kilpatrick et al , 2010 ;Lecat et al , 2011 ).…”
Section: Y 1 Receptorsupporting
confidence: 79%
“…The hY 1 receptor was found to be rapidly internalized upon agonist stimulation by different groups (Fabry et al , 2000 ;Gicquiaux et al , 2002 ;Bohme et al , 2008 ;Ouedraogo et al , 2008 ;Lindner et al , 2009 ;Kilpatrick et al , 2010 ;Lecat et al , 2011 ;Lundell et al , 2011 ), consistent with the results that were obtained for its orthologs in the rat (Holliday and Cox , 2003 ;Pheng et al , 2003 ;Holliday et al , 2005 ;Kilpatrick et al , 2012 ) or guinea pig (Parker et al , 2001(Parker et al , , 2002b. Several studies on the internalization mechanism revealed that the Y 1 receptor undergoes clathrin-dependent endocytosis in an Arr3-dependent fashion and is transported back to the cell membrane, involving direct and indirect recycling mechanisms (Gicquiaux et al , 2002 ;Berglund et al , Pheng et al , 2003b ;Holliday et al , 2005 ;Ouedraogo et al , 2008 ;Kilpatrick et al , 2010 ;Lecat et al , 2011 ).…”
Section: Y 1 Receptorsupporting
confidence: 79%
“…Recycling is generally thought to occur after the agonist has been washed out, but there is evidence for GPCRs recycling back to the plasma membrane both in the presence and absence of agonist (55,56). In our experiments, we could not determine whether the agonist hNPY is recycled with the receptor back to the cell surface or whether it is degraded in lysosomes (23,24).…”
Section: Discussionmentioning
confidence: 82%
“…However, neither the underlying molecular mechanisms nor the intracellular trafficking pathways involved are well known. Recent studies indicate that endogenous Y 1 receptors in SK-N-MC neuroblastoma (23) and guinea pig Y 1 but not Y 2 receptors expressed in CHO cells (24) are internalized. On the other hand, in pharmacological studies, hNPY Y 4 receptors expressed in CHO cells were resistant to desensitization and internalization (25), although in radioligand studies, rat Y 4 receptors expressed in CHO cells were found to be internalized (24).…”
mentioning
confidence: 99%
“…All four NPY family receptors can couple to G i but have also been found to evoke an increase in intracellular Ca 2ϩ (Berglund et al, 2003), contradicting the implication that Y1 and possibly Y5 are class B receptors. In addition, several groups have reported that the Y1 receptor internalizes into endosomes, leading to a rapid recycling of the receptor to the cell surface (Fabry et al, 2000;Gicquiaux et al, 2002), a typical feature of class A receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This may ultimately lead to internalization of the receptor. The Y1 and Y4 receptors have been shown to internalize rapidly upon agonist binding (Fabry et al, 2000;Parker et al, 2001;Gicquiaux et al, 2002;Parker et al, 2002), whereas it has been suggested that Y2 does not internalize or does so very slowly (Parker et al, 2001;Gicquiaux et al, 2002).…”
mentioning
confidence: 99%